Evaluation of the Dangerous Decibels Brazil Program in Workers Exposed to Noise - Bramati, Luciana; Marques, Jair Mendes; Gonçalves, Claudia Giglio Oliveira; Welch, David; Reddy, Ravi; Lacerda, Adriana Bender de Moreira (Frontiers in Integrative Neuroscience, 2022)
Abstract: Noise-induced hearing loss can be avoided by taking preventive measures. Objective: To assess the effectiveness of the Brazilian version of the Dangerous Decibels® program for noise-exposed workers, using the ecological model as an educational intervention plan. Method: Non-randomized interventional study with a quantitative, experimental trial design, conducted at a meatpacking company. The participants were divided into two groups – the first one (n=132, divided into 6 subgroups) received the Dangerous Decibels® Brazil educational intervention (DDBEI) adapted to workers (Reddy et al., 2017), while the second group (n=138, divided into 5 subgroups) received a conventional educational intervention (CEI). The interventions lasted 50 minutes. The Hearing Protection Assessment Questionnaire (HPA-5) was administered before and after the interventions. The five dimensions (attitude, behavior, knowledge, supports, and barriers) were compared using the Student’s t-test for paired data (0.05). Results: After both the DDBEI and CEI training, workers improved significantly in barriers, supports, knowledge, attitudes, and behavior around noise. By chance, the CEI group scored lower in all measures than the DDBEI group before training, and though both groups improved, the difference was maintained after training. Conclusions: The Brazilian version of the Dangerous Decibels® program for noise-exposed workers was effective, influencing positively the factors at different levels of the ecological model. Though the DDBEI was no more effective than the CEI, the CEI participants began at much lower levels, so the effectiveness of the DDBEI may have been underestimated.